Severity of mandibular arch crowding in different sagittal malocclusions - C S Yuvashree; Ravindra Kumar Jain; Arya S Prasad (Wolters Kluwer Medknow Publications, 2022)
Mandibular anterior crowding is caused by a variety of factors. Mandibular incisor crowding can be caused by a number of causes including incisor and molar inclination, early loss of deciduous molars, mandibular growth, and oral musculature. The study was aimed to perform an association of the lower anterior crowding severity with gender and type of malocclusion. The current study was performed in a hospital setup and data about mandibular arch crowding patients were collected from the Records management system of a Private Dental Hospital in Chennai city. All the patient data on Mandibular arch crowding were sourced and tabulated after which statistical analysis with SPSS-IBM was done. Data collection was done over a period from June 2019 to February 2021. The entire study sample size was 634 case records. The result obtained from the statistical analysis was found that nearly 46% of the patients were found to have Mandibular arch crowding with female predilection (50%). The most commonly associated age groups were children than adults (63.2%) associated with mild type of crowding (65.1%). The most commonly involved malocclusion was found to be Class 1 (88.4%) Mild imbrications of the lower arch were common and were seen mainly in subjects with Class I malocclusion. Female subjects presented with more prevalence of mandibular arch crowding when compared to male subjects. Children were more affected by crowding than adults.